A study on technical efficiency of islamic banks before and after financial crisis using Data Envelopment Analysis (DEA): evidence from MENA countries / Mohamad Ilham Mohammad Rosdi and Noor Adilah Nawawi - Mohammad Rosdi, Mohamad Ilham; Nawawi, Noor Adilah (2014)
Purpose- The purpose of this study is to examine the technical efficiency of the Islamic bank in MENA countries before and after financial crisis using Data Envelopment Analysis (DEA). The study measures and compares the level of efficiency of the Islamic Banks in MENA countries in experiencing before and after financial crisis from the 2004 to 2010. Design/ Methodology/ Approach- There are 14 countries to be measure in MENA. The study uses data envelopment analysis (DEA) to measure the relative efficiency of the selected banks in intermediating inputs into outputs. The study the analyses the difference in the average efficiency score of the before and after financial crisis which is 2004 until 2006 are before financial crisis while 2007 until 2010 are after financial crisis. Finding- This study found that the performance of Islamic Banks in MENA countries is outperformed in technical and pure technical efficiency measures. Research limitations/Implications- This study may be extended in various ways. Since, this study only covers a sample period of seven years which are 2004 to 2010, thus future research might cover more sample periods. Further studies could also take a bigger sample size by including broad sample size such as Asia countries. Originality/values- This study identified the most and least efficient of 14 countries in MENA regions before and after financial crisis and the finding could be useful to regulators and the banks as a benchmark in operating the financial industries. This study may also improve the awareness among the least efficient banks to initiate the proactive measures in order to be sustainable in the industry